(untitled) (Bangladesh Journal of Animal Science, 2013)
To investigate the chemeric condition of bulls by cytogenetic analysis the present study was conducted. The whole blood culture, cell harvesting, conventional Giemsa staining and GTG banding were performed for the chromosomal studies. During cytogenetic investigation on 200 buffalo bulls, 3 young bulls exhibited sex chromosomal chimerism (XX/XY) in their blood cells. Hundred metaphase fields were screened for each bull. Cytogenetic studies on chimeric bulls indicated unusual higher ratio of XX chromosomes in 3 bulls. The fertility status of these bulls are not known as they are young and not in semen collection. As documented, the fertility of chimeric bulls is not grossly affected and the condition is not inheritable. Hence, the bulls may be used for breeding programmes if their semen quality is good. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15761 Bang. J. Anim. Sci. 2013. 42 (1): 20-22